ANALISIS KUALITAS LAYANAN ATM DAN KEPUASAN PENGGUNA TERHADAP LOYALITAS PELANGGAN DENGAN PENDEKATAN STRUCTURAL EQUATION MODELLING - Sandra A. Zanny; Deni Danial Kesa (Program Pendidikan Vokasi Universitas Indonesia, 2015)
AbstractThis research has been prepared for the purpose of reviewing the impact of the quality ofservices provided by ATM on one of the largest private bank in Indonesia on customer loyalty. Inthis case the quality of the service will be tested at one of the ATM Bank the largest private bank inIndonesia which consists of quality information and quality on customer loyalty ATM system onone of the largest private bank in Indonesia which is mediated by customer satisfaction. T-countvalue obtained from Confirmatory Factor Analysis (CFA) for all variables showed that all thequestions are included in all variables statistically significant. The coefficient of Goodness of Fitmeets the requirements of the suitability of a model, it can be concluded that in general, the modelobtained has a good level of compatibility. ATM service quality has a statistically significantpositive relationship with customer loyalty. Satisfaction with the quality of the information contentof ATM and satisfaction with the performance of the ATM system did in fact have a positiverelationship with customer satisfaction. Variable satisfaction statistically significant influenced bytwo independent variables, namely variable quality and Quality Information System. Satisfactionwill impact on the confidence of customers to use ATMs that will appear on the ATM customerloyalty to the Bank. In accordance with the hypothesis that the satisfaction variables provide astatistically significant effect on the variable loyalty.Key words : ATM, Confirmatory Factor Analysis,Kandungan informasi, kualitas system, loyalitas